Design of experiments to study the risk of sous vide cooking for possible migration of hazardous compounds from the packaging to the food. Analysis by DI-SPME-GC-MS and UPLC-IMS-QTOF - Jiménez Estremera, Carlos; Paiva, Robert; Borja, Carolina; Nerín, Cristina; Domeño, Celia (Jornada de Jóvenes Investigadores del I3A, 2023)
Using design of experiments (DoE) and response surface methodology, the influence of Sous Vide cooking time and temperature conditions on the migration of volatile and non-volatile hazardous compounds into the food was studied. Migration has been studied in HDPE-PA and PP-PA and in three simulants, analysing the compounds of interest by DI-SPME-GC-MS and UPLC-IMS-QTOF.